Essential surgical practice : higher surgical training in general surgery - Cuschieri, A. (Alfred); Steele, R. J. C.; Moossa, A. R. (London ; New York : Arnold, 2015)
Essential Surgical Practice: Higher Surgical Training in General Surgery, Fifth Edition provides a comprehensive guide for surgical trainees and practitioners focusing on advanced training in general surgery. This edition covers core surgical principles, preoperative and postoperative care, and detailed operative techniques across a range of surgical specialties. The text is structured to offer clear, practical insights into complex procedures and addresses essential topics like trauma management, gastrointestinal surgery, vascular surgery, and oncology. Updated with recent advancements and evidence-based practices, this guide aims to equip surgeons with the knowledge and skills required for high-level clinical practice and surgical decision-making.
GENERAL SECTION -- Surgical Biology and Pathology: Sir Alfred Cuschieri -- Surgical Craft Approaches and Technologies: Sir Alfred Cuschieri -- Risk Assessment and Prognostic Indices in Surgery: Omar Faiz -- Care of the Patient in the Perioperative Period: Helgi Johannsson and Vafa Mansoubi -- Patient-Reported Outcomes to Evaluate Surgery: Jane M. Blazeby -- Intensive and High Dependency Care: Arup Chakraborty, Nicolas Price and Martin Stotz -- Anaemia, Hypovolaemia and Oedema: Sir Alfred Cuschieri -- Cardiovascular Pathophysiology: P. George, J. George and Allan D. Struthers -- Pulmonary Insufficiency: Elizabeth Starren, William Oldfield and Onn Min Kon -- Renal Insufficiency: Neill Duncan and R.W. Corbett -- Surgical Infections and Infestations: Sir Alfred Cuschieri -- Surgical Nutrition: Sir Alfred Cuschieri -- Interventional Radiology in General Surgery: Mohamad S. Hamady -- Trauma and the Injured Patient: Leslie Kobayashi, Raul Coimbra and David Hoyt -- Head Injuries: Pathophysiology and Management: Sam Eljamel -- SPECIALIST GENERAL SURGERY -- Disorders of the Skin and Soft Tissues: Sir Alfred Cuschieri -- Disorders of the Breast: Alistair M. Thompson, Stacy L. Moulder-Thompson, Andrew Evans and John A. Dewar -- Disorders of the Thyroid Gland: S.P. Balasubramanian and David Smith -- Disorders of the Parathyroid Gland: Paul R. Maddox -- Disorders of the Adrenal Glands: G.P. Sadler -- Disorders of the Abdominal Wall, Peritoneal Cavity and Retroperitoneum: Sir Alfred Cuschieri -- Disorders of the Oesophagus: George B. Hanna, Sami M. Shimi and Sir Alfred Cuschieri -- Disorders of the Stomach and Duodenum: Sir Alfred Cuschieri and George B. Hanna -- Disorders of the Liver: Francesco M. Polignano, John F. Dillon, Ian A. Zealley, Aaron J. Quyn, Aileen Smith and Sir Alfred Cuschieri -- Disorders of the Biliary Tract: Sir Alfred Cuschieri -- Disorders of the Spleen and Lymph Nodes: Sir Alfred Cuschieri -- Disorders of the Pancreas: Sir Alfred Cuschieri and Abdool Rahim Moossa -- Bariatric Surgery: Ahmed R. Ahmed and Carel L.G. Roux -- Disorders of the Small Intestine and Vermiform Appendix: Sir Alfred Cuschieri -- Disorders of the Colon and Rectum: Paris Tekkis, Panagiotis Georgiou, Edward Fitzgerald and Emil Tan -- Disorders of the Anal Canal: Ken Campbell
Includes bibliographical references and index.
Keywords: Surgery